Random laser in vitreous matrix with inhomogeneous scatterer distribution and a statistical approach in polymeric nanofiber random laser - Sciuti, Lucas Fiocco (2019)
Random laser has been shown a great alternative to applications in several technological branches such as sensors, portable and flexible devices, miniaturized lasers among others due to the random laser does not need a mirror cavity. Due to its wide utilization, it is important the searching for new materials and architectures concerning gain medium, host matrix or the scatterers and how they are distributed. In this work, we have studied the laser energy threshold dependency as a function of the scatterer center distribution in the random laser system volume for Rhodamine 6G-doped xerogel containing TiO2 scatterers. So, the samples presented a higher scatterer density in one face\'s sample when compared to the opposite face and it was measured the energy threshold with the pumping laser hitting the sample both on the side with greater density of scatterers and on the opposite side at a time. Initially, we measured the energy threshold of 3.6 μJ/pulse for a samples without scatterer centers and we demonstrated a decreasing of 22% in the laser threshold when pumping in the lower scatterer density sample\'s face, and, inversely, an increasing of 85% when the pumping was done in the higher scatterer density side. This effect was attributed to the role scatterers have in each configuration. In a second part, it was studied the random laser property of two Rhodamine B-doped PMMA nanofibers samples with 1% and 5% (m/m) of dye concentration, both produced via electrospinning technique. It was applied the Pearson correlation coefficient in emission spectra to map the laser modes interaction as a function of time in coherent random laser emission, such as monitor the line widening and red/blueshift in the emission band in an incoherent random laser. This correlation method proved to be sensitive to small variations in the spectra. It was also shown the mode-locking transition between an incoherent and a coherent emission just by changing the pumping place in the sample due to different fiber densities that occurs in its fabrication and alters the scattering properties of the material.